2022
DOI: 10.1155/2022/4673514
|View full text |Cite
|
Sign up to set email alerts
|

A Cuproptosis-Related lncRNAs Signature Could Accurately Predict Prognosis in Patients with Clear Cell Renal Cell Carcinoma

Abstract: Background. Clear cell renal cell carcinoma (ccRCC) is the most common subtype of kidney cancers. As cuproptosis, a new cell death mechanism proposed recently, differs from all other known mechanisms regulating cell death, we aimed to create prognostic markers using cuproptosis-related long non-coding ribonucleic acids (RNAs; lncRNAs) and elucidate the molecular mechanism. Methods. Data from transcriptome RNA sequencing of ccRCC samples and the relevant clinical data were downloaded from The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous research has linked FOXD2-AS1 to cuproptosis [35]- [36] and shown that it is highly expressed in ccRCC cell lines [35]. FOXD2-AS1 is aberrantly expressed in various cancers and has been linked to cancer progression [37] via targeting Akt/E2F1 [38], P53 [39] , the microRNA-98-5p/CPEB4 axis [40] and miR-25-3p/Sema4C [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked FOXD2-AS1 to cuproptosis [35]- [36] and shown that it is highly expressed in ccRCC cell lines [35]. FOXD2-AS1 is aberrantly expressed in various cancers and has been linked to cancer progression [37] via targeting Akt/E2F1 [38], P53 [39] , the microRNA-98-5p/CPEB4 axis [40] and miR-25-3p/Sema4C [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed FOXD2-AS1 was associated with many cancers, such as breast cancer, ovarian cancer, retinoblastoma, and cervical cancer. High expression of FOXD2-AS1 could promote the progression of cancer cell, including proliferation, migration, and invasion [31][32][33][34][35], and could be prognostic biomarker for many cancers, such as oral squamous cell carcinoma, head and neck squamous cell carcinoma, renal cancer [36][37][38]. LINC00839 could promote the progression of several cancers, including gastric cancer, neuroblastoma, colorectal cancer, and liver cancer [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether lncRNAs are involved in m6A and cuproptosis remains unknown and their identification may speed up diagnoses and prognoses for ccRCC patients. Recent studies have analyzed m6A and cuproposis-associated lncRNAs in renal cancer [ 35 , 36 ]; however, only a few studies have explored their roles in ccRCC.…”
Section: Introductionmentioning
confidence: 99%